2016
DOI: 10.3892/br.2016.658
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide protects rats from cerebral ischemia/reperfusion injury via a mechanism of action in the MAPK pathway

Abstract: The aim of the present study was to investigate the protective function and underlying mechanism of calcitonin gene-related peptide (CGRP) on cerebral ischemia/reperfusion damage in rats. Adult male Wistar rats were selected for the establishment of an ischemia/reperfusion injury model through the application of a middle cerebral artery occlusion. Animals were randomly divided into 6 groups of 24 animals. Drugs were administered according to the design of each group; animals were administered CGRP, CGRP8–37, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Previous studies have investigated the function of the the MAPK signaling pathways in I/R, including ERK, c-Jun N-terminal kinase (JNK) and p38 pathways. For example, Yang et al ( 20 ) identified that CRGP effectively improved I/R injury of the brain tissue through a reduction in JNK and p38 phosphorylation and an increase in ERK phosphorylation in the MAPK pathway. Zhang et al ( 9 ) demonstrated that ROCK enhanced cardiomyocyte apoptosis in the heart I/R via promotion of JNK-mediated apoptosis-inducing factor translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the function of the the MAPK signaling pathways in I/R, including ERK, c-Jun N-terminal kinase (JNK) and p38 pathways. For example, Yang et al ( 20 ) identified that CRGP effectively improved I/R injury of the brain tissue through a reduction in JNK and p38 phosphorylation and an increase in ERK phosphorylation in the MAPK pathway. Zhang et al ( 9 ) demonstrated that ROCK enhanced cardiomyocyte apoptosis in the heart I/R via promotion of JNK-mediated apoptosis-inducing factor translocation.…”
Section: Discussionmentioning
confidence: 99%
“…It is also clear that MAPK pathway members, including ERK, JNK and p38, serve important roles in neuronal cells as a response to the stress stimuli induced by I/R ( 28 ). Inhibition of ERK by U0126 or PD98059 significantly decreases the number of surviving cells in hippocampal CA1 subfield and cortex ( 29 ), whereas activation of ERK significantly ameliorates neurological deficit and histopathology alterations in rats exposed to 90 min MCAO-induced ischemia and 24 h reperfusion ( 30 , 31 ). The alterations in JNK and p38 appeared to be contrary to ERK, with the inhibition of JNK and p38 attenuating infarction volume in I/R brains in vivo ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the body, production and release of CGRP are likely increased by ischemia and help defend against it . Similarly, in animal models of cerebral ischemia‐reperfusion, intraperitoneal or intravenous administration of CGRP decreases the extent of tissue damage and behavioral deficit . Intravenous CGRP also decreases the lesion size in a mouse model of permanent ischemia .…”
Section: Neuroprotective Consequences Of Cgrp Outside the Blood‐brainmentioning
confidence: 97%
“…In addition, CGRP seems to reduce NMDA‐mediated excitotoxicity . By inhibiting glycogen synthase kinase‐3β, CGRP can prevent hyperphosphorylation of tau and the consequent neural degeneration .…”
Section: Neuroprotective Consequences Of Cgrp Outside the Blood‐brainmentioning
confidence: 99%
See 1 more Smart Citation